2013
DOI: 10.1007/s10265-013-0617-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic reappraisal of Allium subgenus Cyathophora (Amaryllidaceae) and related taxa, with a proposal of two new sections

Abstract: The phylogeny of subgenus Cyathophora and representatives of its closely related taxa within Allium were reconstructed based on nrDNA ITS and two plastid fragments (trnL-F and rpl32-trnL). The constructed phylogenies indicated that subgenus Cyathophora was not monophyletic and to be split in three parts positioned in different clusters. Allium kingdonii was unequivocally placed within subgenus Amerallium and formed an immediate sister relationship with New World Amerallium clade, suggesting an unexpected inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
6
14
0
1
Order By: Relevance
“…(2006) . Yet, consistent with the results of Huang et al. (2014) , A. kingdonii is nested within subgenus Amerallium Traub., as sister to the clade of American Amerallium .…”
Section: Resultssupporting
confidence: 88%
“…(2006) . Yet, consistent with the results of Huang et al. (2014) , A. kingdonii is nested within subgenus Amerallium Traub., as sister to the clade of American Amerallium .…”
Section: Resultssupporting
confidence: 88%
“…Phylogenetic analysis suggested that A. kingdonii is closely clustered with A. paradoxum (Figure 1), which was consistent with a previous study (Huang et al 2014). This complete cp genome can provide a genomic resource and can be further…”
supporting
confidence: 90%
“…He et D.Q. Huang for A. kingdonii was proposed, and A. kingdonii was unequivocally placed into the subgenus Amerallium (Huang et al 2014). In this study, we reported the complete chloroplast genome sequence of A. kingdonii, which will provide a genomic resource and can be used to investigate the phylogenetic relationships in the Allium L. with other previously reported species.…”
mentioning
confidence: 75%
“…In previous study, A. spicatum was classified at different taxonomic levels because of its idiographic spicate inflorescence based on morphological and molecular evidences [3]. Five species have been proposed by Huang et al about subgenus Cyathophora [4]: A. mairei, A. rhynchogynum, A. cyathophorum, A. cyathophorum var. farreri, and A. spicatum, while A. kingdonii and A. trifurcatum did not belong to this group.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [6] performed phylogenetic and biogeographic analyses for A. cyathophorum and A. spicatum based on chloroplast and nuclear ribosomal DNA and detected distinct different topologies between these two molecular methods, in which A. cyathophorum showed close relationship with A. spicatum in nuclear DNA tree but was sister to A. cyathophorum var. farreri in cpDNA tree [4,6]. Other than this, the relationship between these species is not exactly determined, and phylogenetic analysis using single or several combined chloroplast fragments does not solve the problem effectively, and the complete cp genome can well resolve the relationship of subgenus Cyathophora.…”
Section: Introductionmentioning
confidence: 99%